Psychometric Properties of the Five Facet Mindfulness Questionnaire in People - I Sajjadian (پژوهش‌های علوم شناختی و رفتاری, 2016)
The purpose of this research was to determine psychometric properties of the Five Facet Mindfulness Questionnaire (FFMQ), including internal consistency, reliability, convergent and divergent validity. Therefore a group of 500 people from Isfahan city (292 females and 179 males) were selected by multicluster randomize sampling. Participants were asked to complete the Five Facet Mindfulness Questionnaire (FFMQ), the center for epidemiologic studies- depression scale (CES-Q), the satisfaction with life scale (SWLS) and the trait meta-mood scale (TMMS). Data were analyzed using factor analysis through the confirmatory factor analysis. The result of confirmatory factor analysis showed five factors for FFMQ and the model’s goodness of fit indices proved model fitness with the Iranian data. Data were indicative of high level of cronbach's Alpha (0.81) reliability coefficient of FFMQ. The convergent and divergent validity of the questionnaire was examined by measurement tools for CES-Q, SWLS, TMMS and FFMQ and the relation results for the three criteria are sequentially as follow 0.424, 0.257 and 0.588 which are significant at (0.0001). Overall, the results showed FFMQ can be utilized in research and clinical and educational setting for measuring mindfulness.